Effect of an educational intervention based on health belief model on promoting preventive behaviors of needlestick injuries in operating room personnel - Mohammad Bakhshi; Saeed Bashirian; Majid Barati; Yadollah Fathi; Mitra Mitra Zandieh (Tehran University of Medical Sciences, 2020)
Background & Aim: Operating room personnel are always exposed to blood-borne infections because of Needlestick Injuries (NSIs). Thus, this study was conducted to determine the effectiveness of an educational intervention to promote NSIs preventive behaviors among the operating room personnel based on the health belief model (HBM). Methods & Materials: This is an interventional study with a pre-test/post-test, control group design, conducted on 90 operating room personnel (45 personnel in each group) from four hospitals in Hamadan City in 2018. The participants completed a self-administered questionnaire including demographic and professional variables and HBM constructs. The intervention included four educational sessions held for the experimental group within one month. Both groups were followed up for three months after the intervention. Data were analyzed by the SPSS software version 18 using independent t-test, chi-square, Fisher exact test, and analysis of covariance (ANCOVA). Results: The results showed that before the educational intervention, there was no statistically significant difference in the mean scores of HBM constructs between the experimental and control groups (P>0.05). However, after the educational intervention, both the experimental and control groups had a statistically significant difference between before and after changes in the mean scores of knowledge, perceived vulnerability, perceived benefits, perceived self-efficacy, and NSIs preventive behaviors (P<0.05). Conclusion: According to the results, applying the educational intervention based on the HBM is an appropriate and effective approach in preventing NSIs among the operating room personnel.